PLIOCENE ALLUVIAL TO MARINE DEPOSITS OF THE VAL D’ORCIA BASIN (NORTHERN APENNINES, ITALY): SEQUENCE STRATIGRAPHY AND BASIN ANALYSIS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
Since the Middle-Late Miocene, the Apennine chain was characterised by the development of several basins. These basins have been alternatively explained as extensional post-orogenic basins or syn-orogenic compressional basins. In this framework, the Pliocene depositional history of the Val d'Orcia Basin (Southern Tuscany) is described, based on a sequence stratigraphic approach. Three depositional sequences (Vd3a-c) have been recognized. The Vd3a sequence records marine ingression and subsequent relative sea-level highstand in a narrow W-E trending depression. Subsequent relative sea-level fluctuations led to a progressive basin widening and deposition of Vd3b and Vd3c sequences. Basin scale sedimentation was mainly controlled by relative sea-level changes, although accumulation of bioclastic deposits of the Vd3c sequence could have been influenced by climatic factors. Based on its wide bowl-shaped geometry, the Pliocene Val d'Orcia Basin has been interpreted as an inherited depression. This depression is thought to be originated by erosion at the Late Miocene-Early Pliocene transition.
Keywords: Northern Apennines; Val d’Orcia Basin; Facies analysis; Sedimentary basin; Basin geometry; Sequence stratigraphy